Crime in Huntington's disease: a study of registered offences among patients, relatives, and controls. Issue 4 (1st October 1998) - Jensen, Per; Fenger, Kirsten; Bolwig, Tom G; Sørensen, Sven Asger
Abstract : OBJECTIVES: Criminal behaviour has been described as a problem in Huntington's disease, but systematic studies including control groups have been missing. Based on information from Danish registries, rates and types of crime committed by patients with Huntington's disease, non-affected relatives, and controls were studied. METHODS: 99 males and 151 females with Huntington's disease were compared with 334 non-affected first degree relatives (134 men and 200 women) and to matched control groups as to frequencies and types of registered criminal convictions. Due to specific age criteria, the group of relatives comprised only about 9% carriers of the gene coding for Huntington's disease. RESULTS: In male patients, crime rates were significantly increased compared with first degree relatives (RR=2.8) and controls (RR=2.3). All types of crime occurred more often in male patients; more severe crimes (murder, rape, arson) were not reported. Rates of drunken driving were significantly increased compared with relatives (RR=3.8) and controls (RR=7.1). Crime rates were neither increased in female patients nor in male and female first degree relatives. CONCLUSION: The results indicate increased prevalence of criminal behaviour in males carrying the gene for Huntington's disease. The crimes committed seem to be of relatively minor severity and are probably closely linked to the personality changes often seen as a result of the disease process, although depressive reactions to the disease, with secondary alcohol misuse, may also play a part. Environmental and familial factors shared by patients and non-affected at risk persons seem to be of less aetiological importance.